The extent of the atonement a dilemma for reformed theology from Calvin to the consensus (1536-1675) - Thomas, G. Michael, 1955- (Carlisle, UK Paternoster, 1997)
Includes bibliographic references and index.
Based on the author's PhD thesis.
Keywords: Atonement (theology).; History of doctrines -- Reformation